Design of Energy Management and IoT-Based Smart Home Security System Improvement - Chaniago, Muhammad Benny; Alamsyah, Rizky Maulana (CENTRAL ASIA AND THE CAUCASUS, 2022)
Energy Management System and home security are some of the exciting discussions to be developed. Many innovations have been made to control the use of electricity and make it easy for humans to monitor their homes even when they are not at home—one of them containing electronic devices in the house. Home security control devices are now integrated with smartphone devices. This study aims to design energy management and home security system (Smart Home), where homeowners can find out their daily electricity usage and make it easier to secure their home when they leave the house. This home security system can provide information when someone tries to enter the house. This home security system can monitor the house by turning on or off lights, electronic devices, door locks, and garage keys using an Android device as a controller using NodeMCU as a communication tool. The results of this study can show that an android application can help in securing a home. So using Prototype security and control of the electrical device through a smartphone-based microcontroller can make it easy for humans.